Different patterns of pneumothorax in patients with soft tissue tumors treated with pazopanib: A case series analysis. - Hisaki Aiba (Public Library of Science (PLoS), 2021)
To investigate pneumothorax patterns in pazopanib treatment by focusing on the positional relationship between the visceral pleura and metastatic lung tumor, we examined 20 patients with advanced soft tissue tumors who developed lung metastases and underwent pazopanib treatment between 2012 and 2019. Pneumothorax was classified into two types based on the location of the metastatic lesion around the visceral pleural area before pazopanib treatment: subpleural type, within 5 mm from the pleura; and central type, >5 mm from the pleura. We investigated the rates of pneumothorax and the associated risk factors. Five patients experienced pneumothorax (three subpleural and two central types). Cavitation preceded pneumothorax in 83% of patients and led to connection of the cavitated cyst of the metastatic lesion to the chest cavity in the shorter term in patients with the subpleural type. Conversely, a more gradual increase in the cavity size and sudden cyst rupture were observed in the central type. The risk factors for pneumothorax were cavitation after initiating pazopanib and intervention before pazopanib, either ablation or surgery. The location of the metastatic lesions was not a risk factor for the occurrence of pneumothorax. In conclusion, pneumothorax is an adverse event associated with pazopanib treatment. Therefore, attention must be paid to predisposing factors such as the formation of cavitation after pazopanib initiation and previous interventions to the lungs. Moreover, because subpleural pneumothorax tends to occur earlier than the central type, a different time course can be anticipated based on the positional relationships of the metastatic lesions to the visceral pleura.